Syntactic Complexity in the Perceived Credibility of Academic Writing: A Cross-Disciplinary Analysis - Karapetyan, Ruzanna (Bulletin of Yerevan University B: Philology, 2025)
This study examines the role of syntactic complexity in shaping the perceived credibility of academic writing across four disciplines: bioengineering, physics, history, and sociology. Through qualitative analysis of multi-clause constructions in recent research articles, the study explores how syntax aligns with disciplinary conventions and communicative goals. Findings reveal that syntactic complexity serves as a crucial tool for balancing clarity and intellectual rigor. In bioengineering and physics, multi-clause structures emphasize empirical precision and functional relationship. History employs causal and sequential structures to construct coherent narratives, fostering trust in historical interpretation. Sociology utilizes embedded and relational clauses to unravel social dynamics. While scientific disciplines prioritize measurable precision and technical clarity, humanities and social sciences favor contextual richness and narrative coherence. The comparative analysis highlights how syntax reflects intellectual rigor, disciplinary priorities, and audience expectations, contributing to the perceived credibility of scholarly texts.